Double-drug loading upconversion nanoparticles for monitoring and therapy of a MYC/BCL6-positive double-hit diffuse large B-cell lymphoma. (August 2022) - Yang, Yulu; Chen, Rui; Gong, Yi; Yang, Weihu; Li, Ke; Fan, Wuzhe; Gou, Shuangquan; Gao, Pengfei; He, Tingting; Cai, Kaiyong
Abstract: Diffuse large B-cell lymphoma (DLBCL) is a systemic hematological malignancy. Herein, through whole exome sequencing (WES), we found that DLBCL genome changes and expression characteristics are associated with various immune cells. Lenalidomide (Len) is a leading candidate for the immunomodulatory treatment of multiple myeloma in the clinic. Inspired by lenalidomide as an immunomodulatory drug for the treatment of multiple myeloma, we constructed a multifunctional nanoplatform with therapeutic and imaging properties for DLBCL by co-loading lenalidomide and dexamethasone (Dex) with upconversion nanoparticles using a GSH-sensitive linker (named as UCNPs-Len-Dex). In vitro cell experiments proved that the UCNPs-Len-Dex had good biocompatibility and obvious antitumor efficacy. UCNPs-Len-Dex also exhibited excellent anti-tumor efficacy and imaging properties in vivo . RNA sequencing showed that UCNPs-Len-Dex targeted and activated the E3 ligase of CRBN, resulting in IKZF1/3 degradation, which inhibited MYC/BCL6-positive DLBCL and maintained the stability of the immune microenvironment. Therefore, this study provided a new monitoring and therapeutic synergetic strategy for DLBCL.